Evaluation of a new type of nano-sized carbon monoxide donor on treating mice with experimentally induced colitis - Nagao, S.; Taguchi, K.; Miyazaki, Y.; Wakayama, T.; Chuang, Victor; Yamasaki, K.; Watanabe, H.; Sakai, H.; Otagiri, M.; Maruyama, T. (Elsevier, 2016)
Low concentrations of exogenous carbon monoxide (CO) have been reported to be useful for the treatment of various disorders related to inflammation and oxidative stress. However, a number of obstacles make it difficult to use CO in vivo. Among these are, at high concentrations, it is toxic and the fact that it is difficult to control its delivery in the body. Hemoglobin-encapsulated liposomes, Hemoglobin-vesicles (HbV), have the potential for use as a new type of nano-sized CO donor, referred to as CO-bound HbV (CO-HbV). In this study, we investigated the potential of CO-HbV as a CO donor in terms of toxicity and therapeutic efficacy using an experimental colitis model. Toxicological assessments of CO-HbV showed no severe adverse effects including death, and clinical laboratory tests and histopathological changes remained normal for 28 days after the administration of doses up to 1400 mg Hb/kg. We then evaluated the therapeutic efficacies of CO-HbV on dextran sulfate sodium (DSS)-induced colitis model mice. A single administration of CO-HbV at 3 days from beginning of the DSS treatment dramatically improved colitis symptoms, colonic histopathological changes and the duration of survival compared to both saline and HbV administration. In addition, the therapeutic effects of CO-HbV on colitis can be attributed to a decreased level of neutrophil infiltration, the production of pro-inflammatory cytokines and oxidative injuries. Interestingly, it appears that an increase in anti-inflammatory cytokine production contributes, in part, to therapeutic effects of CO-HbV in the treatment of colitis. These safety and efficacy profiles of CO-HbV suggest that it has the potential for use as a drug for treating, not only colitis but also a variety of other disorders associated with inflammation and oxidative stress.